2013
DOI: 10.1038/ijos.2013.49
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy evaluation of a new three-dimensional reproduction method of edentulous dental casts, and wax occlusion rims with jaw relation

Abstract: The article introduces a new method for three-dimensional reproduction of edentulous dental casts, and wax occlusion rims with jaw relation by using a commercial high-speed line laser scanner and reverse engineering software and evaluates the method's accuracy in vitro. The method comprises three main steps: (i) acquisition of the three-dimensional stereolithography data of maxillary and mandibular edentulous dental casts and wax occlusion rims; (ii) acquisition of the three-dimensional stereolithography data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Traditionally, the jaw relations in edentulous individuals are recorded in the clinic using occlusal bases, and an upper model, upper occlusal base, lower model, lower occlusal base, and the labial/buccal surface of the models fixed by occlusal bases must be scanned individually. Thereafter, the ICP algorithm of the common labial/buccal surface that is used for 3D construction of the edentulous jaw model with the jaw relations is implemented 31 . 3D construction of edentulous jaw relations by means of commercial complete denture systems, such as Avadent, Dentaca, and 3Shape, also use occlusal bases that are scanned extraorally 27 – 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the jaw relations in edentulous individuals are recorded in the clinic using occlusal bases, and an upper model, upper occlusal base, lower model, lower occlusal base, and the labial/buccal surface of the models fixed by occlusal bases must be scanned individually. Thereafter, the ICP algorithm of the common labial/buccal surface that is used for 3D construction of the edentulous jaw model with the jaw relations is implemented 31 . 3D construction of edentulous jaw relations by means of commercial complete denture systems, such as Avadent, Dentaca, and 3Shape, also use occlusal bases that are scanned extraorally 27 – 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to measure the accuracy of these devices, and the measurement of working models with calipers is assumed to be the standard. These measurements have been compared with digital measurements …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown how accurate results can be obtained through digital impression techniques . According to the findings of more recent studies, mistakes that previously occurred during the clinical and laboratory phases can now be prevented, owing to the extreme accuracy afforded by digital impression devices, and the repetitions required for conventional impression techniques can now be avoided. Furthermore, obtaining direct digital impressions from edentulous patients is a topic of much discussion because of the displaceability of soft tissues .…”
mentioning
confidence: 99%
“…The reconstruction error directly determines CAD accuracy for complete denture. Previous studies have indicated that the use of a model spatial relation positioning device supported by a dental model 3D scanner (dental articular positioning) and the common regional registration method can control the reconstruction error of jaw relation within one hundred microns [ 1 , 2 ]. However, this method requires respective completion of five scanning operations on the upper jaw model, upper jaw dentures, lower jaw model, lower jaw dentures, and double jaw model/dentures of the complete labial and buccal surface.…”
Section: Introductionmentioning
confidence: 99%